Developing Digital Literacy Networks and Technology’s Impact on Gresik Village Communities - Taufiq Harris; M. Furqon Wahyudi (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze the role of multiple stakeholders in developing digital literacy, its impact on social and economic dynamics, and the challenges encountered in rural contexts. Using a qualitative approach grounded in grounded theory, data were collected through interviews, observations, and documentation. The findings reveal that village stakeholders implement synergistic programs to build a productive and sustainable empowerment ecosystem. The Village Government serves as the primary facilitator by formulating digital literacy programs that promote technological adoption; community leaders act as social catalysts, fostering trust and encouraging citizen participation; the private sector supports by providing market access, digital financial services, and technological innovations aligned with local needs; and academics contribute through Community Service Programs (KKN) that enhance digital literacy capacity. However, residents’ awareness and trust in digital technology remain low, collaboration between users, providers, and platforms is suboptimal, and e-commerce, financial technology, and social media utilization are limited. While digitalization fosters more interactive communication and economic growth for micro and small enterprises, it also risks weakening social ties, creating inequality, and eroding local culture. Overall, digital transformation has improved service efficiency and connectivity, yet it requires sustained trust-building, infrastructure maintenance, and inclusive digital literacy development to ensure long-term impact